Genetic implication of GABAB receptors in the etiology of neurological and psychiatric disorders - Gassmann, Martin; Stawarski, Michal; Antonarakis, Stylianos E.; Bettler, Bernhard (Frontiers in Pharmacology, 2025)
GABAB receptors (GBRs) are G protein-coupled receptors that mediate the actions of the inhibitory neurotransmitter GABA in the central nervous system. Early pharmacological studies with the GBR agonist baclofen and high-affinity antagonists were instrumental in revealing both pre- and postsynaptic functions of GBRs, establishing their critical role in maintaining the excitation-inhibition balance in the brain and highlighting their potential as therapeutic targets. The molecular cloning of GBR subunits enabled the generation of GBR knock-out mouse models, allowing assignment of distinct functions to pharmacologically indistinguishable receptor subtypes and the establishment of causal links between receptor dysfunction and pathological conditions. Advances in high-throughput genomic technologies, particularly whole-exome sequencing, have uncovered hundreds of variants in the genes encoding the GBR subunits, GABBR1 and GABBR2, many of which are linked to neurological and psychiatric disorders. Functional characterization of such variants in recombinant assay systems has revealed both gain-of-function (GOF) and loss-of-function (LOF) mutations, which can now be interpreted in the context of high-resolution structural models of GBR activation. Moreover, proteomic studies have revealed that GBRs form macromolecular complexes with a diverse array of auxiliary proteins that modulate their trafficking, localization, signaling kinetics, and ion channel coupling. Variants in several of these GBR-associated proteins have now also been linked to human disease, with some shown to selectively impair presynaptic GBR functions in relevant mouse models. Here, we review the genetic evidence linking GBR dysfunction to human disease and emphasize the critical role of functional analyses of genetic variants in enhancing diagnostic precision and guiding therapeutic strategies.